Studies on Issues in Political Economy since the Global Financial Crisis - Kai Jäger (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2016)
The dissertation includes four studies broadly connected to the causes and consequences of the Global Financial Crisis of 2007-8 from a political economy perspective. Following the intro-duction, Chapter 2 analyzes the political roots of massive foreign reserves accumulation, which has contributed to the American credit boom before the financial crisis. The study shows that elections tend to explain why democracies have acquired less foreign reserves than authoritarian regimes. Basel III was a regulatory consequence of the Global Financial Crisis, which is scheduled to impose liquidity requirements as a prudential measure for commercial banks. Chapter 3 examines whether these liquidity requirements could have an unintended negative effect on monetary stability. Based on a new dataset of reserve and liquidity requirements, the results show that inflation is more robust to changes in the velocity of money if reserve and liquidity requirements are low. Increases in the velocity of money are associated with higher inflation rates if reserve and liquidity requirements are high. The ability of partisan politics to shape economic policies according to ideological goals has been regularly questioned in an era of globalization and austerity. Chapter 4 suggests that government ideology still has a pronounced impact on economic policy-making based on a sample of OECD and new EU member states. Chapter 5 analyzes why major business leaders in France and Germany have publicly supported the euro in the weeks before a bailout program got enacted by the European Council in July 2011. The study shows that direct corporate interest did not appear to matter. Instead, business leaders appeared to be more likely to join the campaign if they were well-connected in business and political networks. The findings suggest that managers disregarded their short-term economic interest to improve their long-term ties with political decision-makers.
Keywords: D72; D85; E41; E50; F31; H10; H50; 330; Financial Crisis; Political Economy; Foreign Reserves; Political Business Cycle Theory; Veto Players; Basel III; Reserve Requirements; Money Demand; Price Stability; Partisan Politics; Economic Freedom; Euro; Rent-Seeking; Lobbying; Social Network Analysis; Finanzkrise; Wirtschaftswissenschaft; Währungsreserven; Mindestreserve; Politischer Konjunkturzyklus; Veto; Basler Akkord; Geldnachfrage; Preisstabilität; Wirtschaftsliberalismus; Euro; Rent-Seeking; Interessenpolitik; Soziales Netzwerk; Wirtschaftspolitik; Neue politische Ökonomie